Pengaruh Variasi Waktu Fermentasi Terhadap Aktivitas Antioksidan Pada Minuman Kombucha Pulpa Kakao (Theobroma cacao L) - Endang Sri Rahayu; Paulus Hengky Abram (Media Eksakta, 2023)
The purpose of this study is to determine the antioxidant activity based on the effect of fermentation variation time of cocoa pulp kombucha drink (Theobroma cacao L.). The sample used in this study is cocoa pulp obtained from yellow cocoa pods the plantation in Sibualong Village, Balaesang District, Donggala Regency. DPPH method is used to see the reduction of free radical occurs caused by antioxidant compounds in fermented cocoa pulp kombucha drink. Antioxidant activity absorbances measured by UV/Vis will be calculated by regretion equation. The value obtained from the regretion equation shows the IC50 value, if the IC50 value is below 50 ppm it indicates a very strong antioxidant activity and if the IC50 value is above 200 ppm it indicates a very weak antioxidant activity. The study show, there to effect of fermentation variation time of the antioxidant activity which is identified by the increasing of IC50. The study shows, there to effect of fermentation variation time of the antioxidant activity which is identified by the increasing of IC50, with IC¬50 values 3rd, 10th and 14th days respectively are 29,387 ppm, 322,404 ppm, and 215,298 ppm. So the best fermentation time is 3 days which shows the IC50 value less than 50 ppm so that the antioxidant activity is included in the very good category.